Evidence-based Guideline for Therapeutic Drug Monitoring of Vancomycin: 2020 Update by the Division of Therapeutic Drug Monitoring, Chinese Pharmacological Society. (23rd December 2020) - He, Na; Su, Shan; Ye, Zhikang; Du, Guanhua; He, Bei; Li, Dakui; Liu, Youning; Yang, Kehu; Zhang, Xianglin; Zhang, Yingyuan; Chen, Xiao; Chen, Yaolong; et al.
Abstract: Background: Clinical practice guidelines or recommendations often require timely and regular updating as new evidence emerges, because this can alter the risk-benefit trade-off. The scientific process of developing and updating guidelines accompanied by adequate implementation can improve outcomes. To promote better management of patients receiving vancomycin therapy, we updated the guideline for the therapeutic drug monitoring (TDM) of vancomycin published in 2015. Methods: Our updated recommendations complied with standards for developing trustworthy guidelines, including timeliness and rigor of the updating process, as well as the use of the Grading of Recommendations Assessment, Development, and Evaluation (GRADE) approach. We also followed the methodology handbook published by the National Institute for Health and Clinical Excellence and the Spanish National Health System. Results: We partially updated the 2015 guideline. Apart from adults, the updated guideline also focuses on pediatric patients and neonates requiring intravenous vancomycin therapy. The guideline recommendations involve a broadened range of patients requiring TDM, modified index of TDM (both 24-hour area under the curve and trough concentration), addition regarding the necessity and timing of repeated TDM, and initial dose for specific subpopulations. Overall, 1 recommendation was deleted and 3 recommendations were modified. Eleven new recommendations were added, and no recommendation was made for 2 clinical questions. Conclusions: We updated an evidence-based guideline regarding the TDM of vancomycin using a rigorous and multidisciplinary approach. The updated guideline provides more comprehensive recommendations to inform rational and optimized vancomycin use and is thus of greater applicability.